2019
DOI: 10.1101/673293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial DNA Copy Number (mtDNA-CN) Can Influence Mortality and Cardiovascular Disease via Methylation of Nuclear DNA CpGs

Abstract: Background: Mitochondrial DNA copy number (mtDNA-CN) has been associated with a variety of aging-related diseases, including all-cause mortality. However, the mechanism by which mtDNA-CN influences disease is not currently understood. One such mechanism may be through regulation of nuclear gene expression via the modification of nuclear DNA (nDNA) methylation. Methods: To investigate this hypothesis, we assessed the relationship between mtDNA-CN and nDNA methylation in 2,507 African American (AA) and European … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…40 Functional assessment demonstrated that modification of mtDNA CN levels resulted in changes in DNA methylation at specific CpGs and expression levels of nearby genes through knockout of the mitochondrial transcription factor, the protein that regulates mtDNA replication in CRISPR-Cas9. 40 These results provided evidence that mtDNA CN may impact cardiovascular health through DNA methylation and differential expression of specific genes that may impact cell signaling. Further studies are needed to investigate whether DNA methylation and gene expression mediate the effects of mtDNA CN on cardiovascular risks.…”
Section: Discussionmentioning
confidence: 99%
“…40 Functional assessment demonstrated that modification of mtDNA CN levels resulted in changes in DNA methylation at specific CpGs and expression levels of nearby genes through knockout of the mitochondrial transcription factor, the protein that regulates mtDNA replication in CRISPR-Cas9. 40 These results provided evidence that mtDNA CN may impact cardiovascular health through DNA methylation and differential expression of specific genes that may impact cell signaling. Further studies are needed to investigate whether DNA methylation and gene expression mediate the effects of mtDNA CN on cardiovascular risks.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, mtDNA-CN alters gene expression through modifying DNA methylation [13,14]. Recent work from our lab has shown that mtDNA-CN is also associated with nuclear DNA methylation in noncancer settings [15]. Given that DNA methylation can modify gene expression, the current study seeks to explore the potential association between blood-derived mtDNA-CN and gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer cells, mtDNA-CN alters gene expression through modifying DNA methylation (Reznik et al 2016;Sun and St John 2018). Recent work from our lab has shown that mtDNA-CN is also associated with nuclear DNA methylation in noncancer settings (Castellani et al 2020a). Given that DNA methylation can modify gene expression, the current study seeks to explore the potential association between blood-derived mtDNA-CN and gene expression.…”
mentioning
confidence: 99%